2021
DOI: 10.1002/med.21781
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome in cardiovascular diseases: Pathophysiological and pharmacological implications

Abstract: Growing evidence points out the importance of nucleotide‐binding oligomerization domain leucine‐rich repeat and pyrin domain‐containing protein 3 (NLRP3) inflammasome in the pathogenesis of cardiovascular diseases (CVDs), including hypertension, myocardial infarct (MI), ischemia, cardiomyopathies (CMs), heart failure (HF), and atherosclerosis. In this regard, intensive research efforts both in humans and in animal models of CVDs are being focused on the characterization of the pathophysiological role of NLRP3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 176 publications
(266 reference statements)
0
14
0
2
Order By: Relevance
“…Apart from Nlrp3 inflammasome, mitogen-activated protein kinases (MAPK) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) are involved in the pathogenesis of chronic inflammation ( 47 ). In particular, the Nlrp3 inflammasome is a cytosolic multiprotein complex expressed in immune/inflammatory cells as well as cardiovascular system cells, including endothelial cells, myofibroblasts/fibroblasts, and cardiomyocytes, which, through the processing and release of interleukin (IL)-1β and IL-18 and the induction of cell death processes (pyroptosis, apoptosis, and necroptosis), plays a key role in the maintenance of host homeostasis and in sustaining the pathophysiological events underlying CVDs ( 48 ). Conversely, TMAO can release inflammatory factors (caspase-1, IL-1 β) ( 49 ) in a dose-and time-dependent manner by activating the reactive oxygen species (ROS)–thioredoxin-interacting protein (TXNIP) –NLRP3 signaling pathway ( 50 ) and inhibiting sirtun3 (SIRT3) –superoxide dismutase2 (SOD2)–mitochondrial ROS signaling pathway ( 51 ), thereby causing endothelial cell injury and aggravating the formation and development of atherosclerosis.…”
Section: The Molecular Mechanism Of Tmao Aggravating Coronary Atherosclerosismentioning
confidence: 99%
“…Apart from Nlrp3 inflammasome, mitogen-activated protein kinases (MAPK) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) are involved in the pathogenesis of chronic inflammation ( 47 ). In particular, the Nlrp3 inflammasome is a cytosolic multiprotein complex expressed in immune/inflammatory cells as well as cardiovascular system cells, including endothelial cells, myofibroblasts/fibroblasts, and cardiomyocytes, which, through the processing and release of interleukin (IL)-1β and IL-18 and the induction of cell death processes (pyroptosis, apoptosis, and necroptosis), plays a key role in the maintenance of host homeostasis and in sustaining the pathophysiological events underlying CVDs ( 48 ). Conversely, TMAO can release inflammatory factors (caspase-1, IL-1 β) ( 49 ) in a dose-and time-dependent manner by activating the reactive oxygen species (ROS)–thioredoxin-interacting protein (TXNIP) –NLRP3 signaling pathway ( 50 ) and inhibiting sirtun3 (SIRT3) –superoxide dismutase2 (SOD2)–mitochondrial ROS signaling pathway ( 51 ), thereby causing endothelial cell injury and aggravating the formation and development of atherosclerosis.…”
Section: The Molecular Mechanism Of Tmao Aggravating Coronary Atherosclerosismentioning
confidence: 99%
“…These molecular signatures of damage or danger interact with Toll-like receptors, which act as pattern-recognition receptors, leading to the activation of NLRP3 inflammasome, with the eventual release of inflammatory pro-atherogenic cytokines (IL-1β, IL-6 and IL-18) that characterize the acute innate immune response (Fig. 1) [19]. Activation of the NLRP3 inflammasome requires a priming signal that can be generated through exposure to oxLDL-induced TLR-4 dependent signaling leading to nuclear factor κ-B (NFκB)-mediated increased production of pro-IL-18 and pro-IL-1.…”
Section: Lipids Are Essential But Not Sufficient To Promote Atherogenesis: Role Of Innate Immunity and Inflammationmentioning
confidence: 99%
“…7 Many studies have highlighted the association of NLRP3 activation with hypertension and cardiovascular disease. [8][9][10] A recent study demonstrated that through the NLRP3 inflammasome pathway, low-dose lipopolysaccharide (LPS; 2 mg/kg) is sufficient to induce cardiac dysfunction in NLRP3-A350V /CreT mutant mice. 11 NLRP3 mediates IL-1β expression and release, but the mechanism by which NLRP3 participates in regulation of the myocardial immune microenvironment in the inflammatory state by mediating the interaction between cardiomyocytes and macrophages has not yet been reported, and whether the NLRP3 inflammasome pathway contributes to RVF and the underlying mechanisms are largely unknown.…”
Section: Introductionmentioning
confidence: 99%